1991
DOI: 10.1111/j.1365-2125.1991.tb03949.x
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of the calcium antagonist, nifedipine.

Abstract: 1 Central effects of the calcium antagonist, nifedipine retard (10, 20 and 40 mg) and nifedipine capsules (10 mg) were studied in 14 healthy male subjects. Two placebos and an active control drug, oxazepam (15 mg), were included. Medication was administered double-blind at 10.00 h. The effects of drugs on performance and subjective feelings were assessed before and from 1.5-2.5 h and 3.5-4.5 h after ingestion, and recordings of the electrical activity of the brain (EEG) and body sway carried out. (15 mg) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…We have also previously demonstrated that this dose of atenolol produces EEG changes consistent with sedation [2]. Nifedipine retard 20 mg used alone produced no significant effects on performance, physiological measurements and subjective awareness, which is also in keeping with our previously published observations [3]. Significant improvements in continuous attention and body sway occurred using the two agents in combination, with no evidence of any adverse central effects.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We have also previously demonstrated that this dose of atenolol produces EEG changes consistent with sedation [2]. Nifedipine retard 20 mg used alone produced no significant effects on performance, physiological measurements and subjective awareness, which is also in keeping with our previously published observations [3]. Significant improvements in continuous attention and body sway occurred using the two agents in combination, with no evidence of any adverse central effects.…”
Section: Discussionsupporting
confidence: 75%
“…This is a well-recognised effect of nifedipine [3], and suggests reflex activation of the sympathetic nervous system due to drug-induced peripheral vasodilatation. The response was abolished in the presence of concomitant/~-adrenoceptor blockade.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The central effects of acute administration of nifedipine have been studied in 14 healthy male subjects using a range of psychomotor tests [54]. No significant effect was seen on digit symbol substitution test, continuous attention test, letter cancellation, choice reaction time, finger tapping, short-term memory and critical flicker fusion frequency suggesting that alertness and performance were not reduced by nifedipine.…”
Section: Calcium-channel Antagonistsmentioning
confidence: 99%
“…It may be that the drug effects are species-specific, but it also possible that the effects are only seen at critical dose levels or are sensitive to variations in testing procedures. With respect to the cognitive effects of calcium antagonists in non-hypertensive volunteers, McDevitt et al (1991) employed a double-blind comparison of nifedipine and oxazepam with placebo in 14 healthy men, and found no acute effects of a single dose of nifedipine on tests of attention, memory or other psychomotor functions.…”
Section: Introductionmentioning
confidence: 99%